From YouTube to TikTok: Speech Acts and Implicatures in Cryptocurrency Influencer Discourse and Its Clipper-Mediated Recontextualization - Azael Umbu Sogara; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon Awololon (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid growth of social media has transformed financial communication, enabling influencers to shape public understanding of cryptocurrency through language that is continuously reproduced and reinterpreted across digital platforms. This study investigates speech acts and conversational implicatures in Timothy Ronald’s cryptocurrency discourse and examines how his YouTube utterances are recontextualized through TikTok clipper accounts and audience responses. Grounded in cyberpragmatics, the study employed a qualitative descriptive design. Thirty utterances were collected from YouTube and TikTok, of which eight representative utterances were purposively selected for in-depth analysis. The utterances were analyzed using Speech Act Theory (Austin, 1962; Searle, 1969), Conversational Implicature Theory (Grice, 1975), and thematic analysis (Braun & Clarke, 2006). The findings reveal that Timothy Ronald’s YouTube discourse is characterized primarily by assertive and directive speech acts that construct authority, display investment conviction, and promote long-term financial perspectives. Several implicature patterns emerged from the analysis, including aspirational, authority-building, conviction-display, authority-amplification, FOMO-related, satirical, humorous, and solidarity-building meanings. The findings also demonstrate that TikTok clipper accounts actively reshape the pragmatic force of the original utterances through amplification, reframing, and audience interaction, transforming authoritative discourse into a negotiated communicative space. The study contributes to the development of cyberpragmatics by demonstrating how speech acts and conversational implicatures are reconstructed through cross-platform recontextualization in financial influencer discourse, thereby extending existing understanding of digital pragmatic meaning-making in the Indonesian context.